The Usability of Big Data in Statistical Studies of the Population in the Conditions of War - O. HOROBETS; S. CHERVONA (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2023)
The war in Ukraine aggravated economic, social, geopolitical, and environmental problems, caused a devastating blow on physical and mental health of the Ukrainian population, worsened its quantitative and structural parameters. Apart from violations of human rights and the occurrence of mental traumas among adults and children alike, terrorist methods of warfare used by the Russian Federation led to heavy losses of the civil population and forced replacements in search for  safety.The conventional problems of the Ukrainian official statistics were added by another one posed by the war: the impossibility to study the population and their living standards in the conditions of war. The authors drew attention to the need to fill the gaps in statistical data by use of alternative war-specific sources in course of the statistical studies of the population. When investigating the issue of implementing big data in the social and demographic statistics, emphasis was made on the methods that could be fit for practical applications now: analysis of surveys, analysis of social media, analysis of health data, geospatial analysis and population analysis. The study allowed for highlighting issues of using microdata, intellectual analysis of text or machine training by the official statistics. It was revealed that the issue of implementing data in the official statistics, for population studies in particular, was but a matter of time, considering the rapid development of digitalizing processes in Ukraine.